A Galáxia de Lucas: sociabilidade e narrativa nos jogos eletrônicos - Andrade, Luiz Adolfo de Paiva (2008)
This work intends to contribute for the reflection concerning the new communicational possibilities and narratives of the digital way, having as central focus the electronic games for multiple users MMORPG. The axle of this work turns around two questions that establishes connection of sufficiently narrow form, still little explored in academic research in the field of the Communication. The first one is the reflection around the experience to play SWG and of the specific contribution of the computer as Comunicative enviroment. At the same time, becomes essential to insert the electronic game in the amplest context of the informacional or postindustrial period of the contemporary society. The second question that will be focused is the modality of sociability staged for the players. Here, the work retakes the quarrel on virtual communities, perceiving that the basic characteristics of these groupings modernize in this experience from the expression guilda , that it is inside translates the form of belonging of the player to a group of the game. To develop quarrel, a study of the case of Star War Galaxies, MMORPG developed for the LucasArts since 2003 is considered. The proposal of this game consists of the recriation of a virtual universe that searchs to simulate the atmosphere of the Star War movies. This action can become realizable the desire of the innumerable fans of the Star Wars s brand: to be able to live, exactly that virtually, in the galaxy conceived by George Lucas.